THE EFFECT OF CONCEPTUAL CHANGE APPROACH ON THE 10TH GRADE ENVIRONMENT AND COMMUNITY LEARNING AREA ON THE ACADEMIC ACHIEVEMENT OF STUDENT (Third Sector Social Economic Review, 2020)
This research aims to determine the misconceptions of the 10th grade students of secondary education in the fields of Environment and Society learning and to eliminate them with a conceptual change approach. The study group of the research consisted of students from two branches studying in the 10th grade of a high school in the city center of Ankara. In the research, semi-experimental method was used. One of the classes included in the study was assigned as control (n = 24) and the other as experimental group (n = 24). In the experimental group, activities supported with conceptual change texts and concept maps were carried out in accordance with the conceptual change approach in the teaching of the environment and community learning area, apart from the program based education, while only the program based education was conducted in the control group. In order to collect data in the research, Academic Achievement Test was applied, and interviews and in-class observations were made with teachers. One-way analysis of variance was used in the analysis of pre-test and post-test scores of experiment and control group students. As a result of the analyzes, it was determined that there was no statistically significant difference between the experimental and control groups in terms of success in understanding the concept, and there was a significant difference in favor of the experimental group in the post-test. As a result of the research, it was concluded that activities supported with conceptual change approach were more effective than only program based teaching in the teaching of environment and community learning area. Therefore, the use of the conceptual change approach in geography teaching may be recommended to other practitioners.
Keywords: Geography teaching; concept; concept teaching; conceptual change approach.